DEVELOPING PROFESSIONAL COMPETENCIES OF FUTURE TEACHERS - Ortikov Umidjon Xudoyberdiyevich (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2023)
This article discusses the formation and content of professional competence in future vocational education teachers, the role and importance of basic competencies in their preparation for professional activity, the mechanism of formation of students' knowledge, skills and competencies in general and specialized disciplines through interdisciplinary relations. and issues such as the integrative-differential approach.